First multicenter experience using the Silk Vista flow diverter in 60 consecutive intracranial aneurysms: technical aspects. (8th April 2021) - Martínez-Galdámez, Mario; Onal, Yilmaz; Cohen, José E; Kalousek, Vladimir; Rivera, Rodrigo; Sordo, Juan Gabriel; Echeverria, Daniel; Pereira, Vitor M; Blasco, Jordi; Mardighian, Dikran; Velioglu, Murat; van Adel, Brian; et al.
Abstract : Background: The aim of this study was to assess the technical success and procedural safety of the new Silk Vista device (SV) by evaluating the intraprocedural and periprocedural complication rate after its use in several institutions worldwide. Methods: The study involved a retrospective review of multicenter data regarding a consecutive series of patients with intracranial aneurysms, treated with the SV between September 2020 and January 2021. Clinical, intra/periprocedural and angiographic data, including approach, materials used, aneurysm size and location, device/s, technical details and initial angiographic aneurysm occlusion, were analyzed. Results: 60 aneurysms were treated with SV in 57 procedures. 66 devices were used, 3 removed and 63 implanted. The devices opened instantaneously in 60 out of 66 (91%) cases and complete wall apposition was achieved in 58 out of 63 (92%) devices implanted. In 4 out of 66 (6%) devices a partial opening of the distal end occurred, and in 5 (8%) devices incomplete apposition was reported. There were 3 (5%) intraprocedural thromboembolic events managed successfully with no permanent neurological morbidity, and 4 (7%) postprocedural events. There was no mortality in this study. The initial occlusion rates in the 60 aneurysms were as follows: O'Kelly–Marotta (OKM) A in 34 (57%) cases, OKM B in 15 (25%) cases, OKM C in 6 (10%) cases, and OKM D in 5 (8%) cases. Conclusions: Our study demonstrated that the use of the new flow diverter Silk Vista for the treatment of intracranial aneurysms is feasible and technically safe.